The Impact of EMNEs' Home Country Learning on Their Internationalization: Evidence from SAIC - Hu, Yuhan (2022)
As companies from emerging market countries increasingly participate in international competition, international business scholars have begun to pay attention to the international operations of emerging market multinational enterprises (EMNEs). Multinational companies from emerging market countries are often considered to lack competitive advantages during internationalization and rely more on the policy support of their home countries to explore markets in other countries. However, the fact that these companies can also accumulate the experience and capabilities required for internationalization through practice, development, and learning in their home countries is overlooked by many scholars. By reviewing previous theoretical and empirical studies on EMNEs internationalization, this research develops several propositions from the perspective of institution-based view and organizational learning, pointing out the effects of the different home country learning on EMNEs’ internationalization. Taking the development history of SAIC as a case, it was used to analyzes the link between home country learning and internationalization: the experience and capabilities acquired by EMNEs in the process of interacting with their home countries and institutions (especially intellectual property protection regimes) can help them operating in other emerging market countries; the characteristics of EMNEs' joint ventures in home countries and foreign capital may make them seek similar cooperation when internationalizing; EMNEs' experience in building complex and well-established business networks in home countries help them operate internationally.